Clinical Efficacy and Safety of Ivacaftor/Lumacaftor Combination in Patients with Cystic Fibrosis: International Studies Review - Nataliya Yu. Kashirskaya; Nika V. Petrova; Rena A. Zinchenko (Вопросы современной педиатрии, 2021)
Cystic fibrosis is an autosomal recessive disease caused by structure abnormalities in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. It is characterized by severe course and poor prognosis without or with insufficient treatment. Approval of pathogenetic therapy medications, CFTR modulators (potentiators and correctors), for clinical use in 2012 in the United States has reduced mortality from this disease. This article provides the overview of studies on clinical efficacy and safety of ivacaftor/lumacaftor combination (Iva/Lum) — the first licensed CFTR modulator medication for homozygous patients with F508del variant. It was shown that Iva/Lum increases lung function, reduce the number of acute conditions of bronchopulmonary process (including those that require antibiotics and hospitalization), partially restores pancreas exocrine function, increases body weight and mass growth index, and improves quality of life. It allows considering it as favorable effect on the course and prognosis of cystic fibrosis. It was also noted that the early onset of the drug administration (from the age of two) positively affects the prognosis of the disease, increasing life expectancy and improving quality of life.